Tumor-infiltrating lymphocytes dan Peranannya pada Karsinoma Payudara - Ditha Diana; Kusmardi (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
Infiltration of T lymphocyte cells in tumor tissue is a good prognosis in cancer patients. The infiltrating lymphocyte(TIL) tumor is the phenotype of CD4+ T lymphocytes and CD8+ T lymphocytes that infiltrate tumors. TIL can have abeneficial effect as well as a detrimental effect on breast carcinoma. There are three subtypes of T lymphocytes thatinfiltrate tumors which are T-helper (Th), T-citotoxic (Tc) and T-regulators (Treg). The role of Th lymphocytes in tumorimmunity can be divided into three phases, that are the initial induction phase, the phase maintaining the Tc responseas an effector and the memory formation phase. Th lymphocytes will secrete cytokines that can stimulate tumor cellsto increase the expression of MHC class I molecules, so that it will further optimize the function of Tc lymphocyticcytotoxicity which has the most dominant role in cytolytic tumor cells. Treg lymphocytes effectively suppressantitumor responses from Tc lymphocytes and other immune cells so that they can facilitate tumor development. Inbreast carcinoma, Treg lymphocytes have a different influence on each of the cancer subtypes.